Automated assessment system for programming courses: a case study for teaching data structures and algorithms - Barczak, Andre L. C.; Mathrani, Anuradha; Han, Binglan; Reyes, Napoleon H. (Educational technology research and development, 2023)
An important course in the computer science discipline is ‘ Data Structures and Algorithms’ (DSA). The coursework lays emphasis on experiential learning for building students’ programming and algorithmic reasoning abilities. Teachers set up a repertoire of formative programming exercises to engage students with different programmatic scenarios to build their know-what, know-how and know-why competencies. Automated assessment tools can assist teachers in inspecting, marking, and grading of programming exercises and also support them in providing students with formative feedback in real-time. This article describes the design of a bespoke automarker that was integrated into the DSA coursework and therefore served as an instructional tool. Activity theory has provided the pedagogical lens to examine how the automarker-mediated instructional strategy enabled self-reflection and assisted students in their formative learning journey. Learner experiences gathered from 39 students enrolled in DSA course shows that the automarker facilitated practice-based learning to advance students know-what, know-why and know-how skills. This study contributes to both curricula and pedagogic practice by showcasing the integration of an automated assessment strategy with programming-related coursework to inform future teaching and assessment practice.